Instant Stent-Accentuated Three-Dimensional Optical Coherence Tomography Guided Selection of Proper Distal Cell for Side Branch Dilatation in Bifurcation Stenting - Fumiaki Nakao (Case Reports in Cardiology)
In the bifurcation stenting, the distal rewiring for the side branch postdilatation confirmed by two-dimensional modalities may not lead to favorable results in some cases. If there are two distal cells divided by the link bridging from the carina, the rewiring through the larger distal cell may be recommended for the side branch postdilatation. Detailed confirmation of the rewired cell by the intraprocedural instant stent-accentuated three-dimensional optical coherence tomography is important.